Decreased pituitary hormone levels in a sheep with pituitary abscess - Dabak, Murat; Eroksuz, Yesari; Baydar, Ersoy; Eroksuz, Hatice; Cevik, Aydin; Muz, Adile (Taylor & Francis Ltd, 2016)
A four-year-old Akkaraman ewe was presented to the Firat University Veterinary Teaching Hospital for circling, dullness, weakness and sternal recumbency. On physical examination, opisthotonus, mydriasis in the right eye and myosis in the left eye, absence of the pupillary reflex, ruminal tympany were detected. Serum pituitary hormone analyses indicated the hypopituitarism characterized by thyroid stimulating hormone (TSH) < 0.05 IU/L, follicle stimulating hormone (FSH) < 0.13 IU/L, luteinizing hormone (LH) < 0.10 IU/L and prolactin (PRL) < 0.50 ng/ml. On the basis of clinical presentation and hypopituitarism, tentative diagnosis of pituitary abscess was made. The animal was euthanized due to the poor prognosis. Morphological examination revealed coexistence of hypophyseal-carotid rete abscess and hyaline thrombosis in carotid rete, heteropic ossification in carotid rete and tuberal muscles. Microbiologically; Arcanobacterium pyogenes was isolated in blood agar culture from the hypophysis. Decreased serum pituitary hormone levels including TSH, FSH, LH and PRL in conjunction with the clinical findings were a useful diagnostic tool for antemortem diagnosis of pituitary abscess in the sheep.
Keywords: basilar empyema; pituitary abscess; pituitary hormones; sheep